The analysis of underivatized β-Methylamino-L-alanine (BMAA), BAMA, AEG & 2, 4-DAB in Pteropus mariannus mariannus specimens using HILIC-LC-MS/MS. (15th September 2018) - Foss, Amanda J.; Chernoff, Neil; Aubel, Mark T.
Abstract: β-Methylamino-L-alanine (BMAA) has been identified as the potential cause of the amyotrophic lateral sclerosis/parkinsonism–dementia complex (ALS/PDC) observed in the Chamorro people of Guam. The principal hypothesis for BMAA exposure and intoxication relies on the biomagnification of BMAA in flying fox specimens ingested by the Chamorro people. Although high levels of BMAA were quantitated in flying fox specimens utilizing liquid chromatography-fluorescence (LC-FL), there have not been any confirmatory analyses conducted to date. Therefore, a method for the tissue homogenization, extraction and direct analysis of BMAA (including BAMA, 2, 4-DAB and AEG) was utilized. The approach was applied to mammalian dried skin and hair from various rodent species (negative controls) and archived flying fox ( Pteropus mariannus mariannus ) specimens. A positive control sample of homogenized mussel ( Mytelius edulis ) with native BMAA was used to verify the method. It was determined that the direct analysis using HILIC MS/MS required additional quality control in order to allow for the confident identification of BMAA due to the near co-elution of BAMA. BMAA was not present above 0.2 μg g −1 (free fraction) or 2.8 μg g −1 (total fraction) in the flying fox specimens. While analysis did not result in BMAA detection in flying fox or negative control samples, the positive control sample and spiked samples were successfully detected. Graphical abstract: Image 1 Highlights: Pteropus mariannus mariannus specimens (skin with hair) from Guam were extracted and analyzed for BMAA. BMAA was not detected in samples that were analyzed using direct analysis (HILIC LC-MS/MS). Samples previously reported to have BMAA using LC-FL should be reassessed.